Implementasi Model Project Based Learning dalam Meningkatkan Keterampilan Menulis Bahasa Jerman - Misnawaty Usman; Syukur Saud; Nurming Saleh; Suhelmi Mifta Sukri (Phonologie : Journal of Language and Literature, 2025)
Abstract. This research is classroom action research which aims to determine the planning, implementation and description of the implementation results of the Project Based Learning model in improving the writing skills of class XII MIPA 5 students at SMA Negeri 13 Bone. In this research, there are two types of data, namely qualitative data which describes the results of implementation and observation during the teaching and learning process, and quantitative data which is the results of tests on students German writing skills. Based on the results of data analysis, the average value in cycle 1 was 69.76 and in cycle 2 there was increase to 81.29.  From the results of this research, it can be stated that the Project Based Learning model can improve students German writing skillsKeyword: Project Based Learning model,  Writing Skills, German